Continuous and controllable preparation of polyaniline with different reaction media in microreactors for supercapacitor applications. (2nd November 2019) - Song, Yang; Liu, Saier; Wang, Baoyi; Shang, Minjing; Lin, Liangliang; Su, Yuanhai
Highlights: Conductive polyaniline particles were prepared with various media in microreactors. Reaction media influenced the microstructure variation of polyaniline particles. Morphology accorded with Hansen's solubility parameters and Flory-Huggins theory. Supercapacitor electrodes using prepared polyaniline had excellent performance. Abstract: Polyaniline (PANI) particles were prepared via chemical oxidative polymerization in microreactors within the liquid-liquid slug flow regime. The effect of co-solvent (methanol, glycol or glycerol) on the morphology, chemical structure, thermal stability and electrochemical performance of final polymer products was investigated. Hansen's solubility parameters and Flory-Huggins model were introduced to explicate the microstructure variation of PANI particles synthesized with different media. The characteristic dimension of PANI particles tended to be smaller with the decrease of the Flory parameter of the reaction medium. Electrochemical measurement indicated that the specific capacitance of PANI could be improved by adding an organic co-solvent into the reaction medium. The maximum specific capacitance of 426F/g was achieved at the current density of 1 A/g with the voltage window ranging from −0.2 to 0.8 V (vs. Ag/AgCl) in 1 M H2 SO4 solution. The maximum energy density reached 59.2 Wh/kg with the power density of 500 W/kg.